2001
DOI: 10.1159/000048630
|View full text |Cite
|
Sign up to set email alerts
|

Event-Related Evoked Potential P300 in Frontotemporal Dementia

Abstract: There are no studies on event-related cognitive potentials in frontotemporal dementia (FTD). In order to evaluate the aptitude and usefulness of the event-related P300 potential in this disease, we prospectively examined 60 cases: 11 patients with FTD diagnosed according to the Lund and Manchester criteria and Neary consensus criteria, 33 patients with a probable Alzheimer’s disease diagnosis following NINCDS-ADRDA criteria, and 16 normal controls. P300 latency, amplitude and reaction time were recorded using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 28 publications
0
8
0
2
Order By: Relevance
“…Renal hypoxia is known to stimulate the production of cytokines such as hypoxia-inducing factor-1, which contributes to renal scarring 20. In addition, hypoxia stimulates renal sympathetic activity, resulting in reduction of renal blood flow and eGFR over time 21; therefore, anaemia and renal interstitial fibrosis could have a cause-and-effect relationship with each other. Our multivariate analysis showed that IFTA score was strongly associated with both the decrease in haemoglobin and the baseline haemoglobin level, which may support such a cause-and-effect relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Renal hypoxia is known to stimulate the production of cytokines such as hypoxia-inducing factor-1, which contributes to renal scarring 20. In addition, hypoxia stimulates renal sympathetic activity, resulting in reduction of renal blood flow and eGFR over time 21; therefore, anaemia and renal interstitial fibrosis could have a cause-and-effect relationship with each other. Our multivariate analysis showed that IFTA score was strongly associated with both the decrease in haemoglobin and the baseline haemoglobin level, which may support such a cause-and-effect relationship.…”
Section: Discussionmentioning
confidence: 99%
“…In the kidney, renal sympathetic nerve activity contributes to the regulation of renal blood flow, glomerular filtration rate, electrolyte transport and hormonal release. Recently, Denton et al [44] have reported that an increase in renal sympathetic nerve activity triggered by hypoxia caused a decrease in renal blood flow in rabbits, whereas glomerular capillary pressure was increased without affecting the mean arterial blood pressure. The calculated preglomerular and postglomerular resistance both showed an increase, but only the increase in postglomerular resistance was significant.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, overexpression of AEBSs and high affinity of tamoxifen to AEBS are speculated to be involved in acquired tamoxifen resistance in the presence of continued ER expression .AEBSs do not bind either to endogenous estrogens or the steroidal antiestrogens, but binds to tamoxifen, which belongs to the non-steroidal antiestrogens (Pavlik et al ., 1992). It has also been reported that the affinity of tamoxifen for AEBS is particularly high at the 1 nM level, which is significantly greater than its affinity for the ER (Denton et al ., 2002).…”
Section: Mechanisms Of Endocrine Resistancementioning
confidence: 99%